A cross-sectional qualitative interview to describe the feelings of young men and character identification when playing Call of Duty: Modern Warfare (2019) Campaign - Bothma, Cindy (The IIE, 2020)
The study aimed to describe the feelings of young men when playing Call of Duty: Modern Warfare (2019 as well as describe how the participants identified with their in-game character. The theoretical framework was Gerrig (1993) Transportation Theory which aided the study by providing central components that was used to gather an understanding as to why the participants experienced certain feelings and how they identified with their in-game character. The data collection method included the use of a structured interview in order to ensure that all participants were asked the same questions within the same format. The data was analyzed thematically in order to develop the necessary themes based on the similarities found within the participants responses. The findings were presented in two themes, “Feelings” and “Character Identification”. The findings included both negative and positive feelings associated with the game and that majority of the participants did not experience character identification. The study will contribute towards the Communication field, specifically in studies relating to the gaming community as well as the society field based on a qualitative description.
Keywords: Young men; Character identification; Feelings; Call of Duty: Modern Warfare (2019) Campaign; Gaming